2021
DOI: 10.2139/ssrn.3781534
|View full text |Cite
|
Sign up to set email alerts
|

Occupation and Working Outcomes During the Coronavirus Pandemic

Abstract: Using data from the recent SHARE COVID-19 survey and additional information collected in the previous waves of SHARE, we explore the effects of occupation's characteristics on two outcomes: (i) the probability of work interruptions during the pandemic, coupled with the length of such interruptions and (ii) the probability of switching to homeworking during the lockdown. In order to assess how job features affected the likelihood of having experienced work interruptions or shifted to teleworking, we define six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…Our study corroborates that financial concerns are associated with mental health declines of ageing workers, as demonstrated among working, non-working and retired elderly population during the pandemic, and the general population during the pandemic 17 19 22. In addition, the lower technological skills of many ageing workers may hinder teleworking as a control measure, resulting with their prolonged work interruption during the pandemic and its related financial consequences, as Brugiavini et al demonstrated using SHARE 49…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our study corroborates that financial concerns are associated with mental health declines of ageing workers, as demonstrated among working, non-working and retired elderly population during the pandemic, and the general population during the pandemic 17 19 22. In addition, the lower technological skills of many ageing workers may hinder teleworking as a control measure, resulting with their prolonged work interruption during the pandemic and its related financial consequences, as Brugiavini et al demonstrated using SHARE 49…”
Section: Discussionsupporting
confidence: 88%
“…17 19 22 In addition, the lower technological skills of many ageing workers may hinder teleworking as a control measure, resulting with their prolonged work interruption during the pandemic and its related financial consequences, as Brugiavini et al demonstrated using SHARE. 49 sociodemographic inequalities Differentiated occupational infection risk, which we demonstrated to affect mental health, cannot be isolated from sociodemographic inequalities that characterise workers in different industries, for example, gender. 50 Being a woman almost doubled the odds of worsening mental health in our study.…”
Section: Socioeconomic Concernsmentioning
confidence: 78%
See 1 more Smart Citation
“…15 Moreover, job disruption appears not to have a significant effect on reporting worsened symptoms of psychological distress also in the group of countries characterized by a lower level of employment protection (EPL cluster=1 in Table 5). weeks, equal to the median value of the variable and excluding from the sample workers who experienced job disruption for 8 weeks or less (9.3 % of the full sample) (see also Brugiavini et al 2021). Then, the propensity score was computed through a Probit model for those who experienced more than 8 weeks of job disruption, using the same specification as described in Section 3.…”
Section: Resultsmentioning
confidence: 99%